System dynamics modeling for developing an agrotourism-creative economy in the framework of the village innovation system - Santoso, Sugeng; Widyanty, Winda; Nurhidajat, R.; Ramadhani Marfatah, Muhammad; Mahmud, Gustofan; Fahlevi, Mochammad; Aljuaid, Mohammed; Zhghenti, Tsotne; Shahid, Duaa (Frontiers in Environmental Science, 2022)
Cibodas Village is one of the villages in the Regency of West Bandung, which has potential for agrotourism and a creative economy. However, the dynamic environmental changes in the post-COVID-19 era have presented challenges to developing these economic potentials. Therefore, creating a model to develop agro-tourism and creative economy in Cibodas Village is necessary. This study aims to create a system dynamics model with a causal circle diagram based on the village innovation system framework to develop the agrotourism-creative economy in Cibodas village. This study employed an innovation system framework with qualitative and quantitative approaches to explore and create such a model. We used an in-depth interview with key informants and other stakeholders as a qualitative approach. We use system dynamics modelling to execute the quantitative approach and involve three variables: general innovation infrastructure, specific industry clusters, and intermediation. The three variables are interrelated and form a causal circle diagram (CLD). To run the simulation, CLD required a stock and flow model in the system for which a stock flow diagram (SFD) was made. The validation test determined the suitability of the model to the real system. Based on the results of the scenario for the existing conditions for a 24-month period, it was found out that the innovation infrastructure variables had increased by 10.94%, and the intermediation variables had increased by 0.22%. The simulations were carried out by increasing the intermediation intervention twice as much as that of the existing conditions. Hence, the innovation infrastructure variables increased by 18.01%, and the Intermediation variables increased by 0.05%. Cibodas Villlage would take advantage of these R&D products to help its creative economy actors produce more products having a high selling value. Moreover, by employing this strategy, they could also help their creative economy actors increase the absorption of an innovation in order to have such a high competitiveness.